Intraoperative Electrical Nerve Stimulation as a Prognostic Tool in Patients Undergoing Peripheral Nerve Neurolysis - Christoph A. Schroen, BS; Yufan Yan, MD; Christian E. Awah, MD; Unwana Abasi, MD; Paul J. Cagle, MD; Michael R. Hausman, MD; Steven M. Koehler, MD (Journal of Hand Surgery Global Online)
Purpose: Functional recovery from peripheral nerve injuries remains unpredictable and continues to pose a major clinical challenge to surgeons. This study sought to investigate the utility of intraoperative nerve stimulation following neurolysis surgery as a prognostic indicator of functional recovery. Methods: A retrospective chart review of adult patients who underwent peripheral nerve neurolysis between September 2021 and December 2022 was performed. A handheld nerve stimulator was used intraoperatively before and after neurolysis. Patients with preoperative motor deficits corresponding to the nerve that underwent neurolysis, intraoperative nerve stimulation, and postoperative follow-up length of at least 3 months were included. Muscle strength as measured by the Medical Research Council scale was used to evaluate nerve function. A scale grade of 0 or 1 meant “no recovery,” between 2 and 4 was classified as “partial recovery,” and 5 was classified as “full recovery.” Fisher exact tests were employed to test for an association between stimulation thresholds and functional recovery. Results: A total of 27 patients and 45 nerves were included in the study, with a mean follow-up of 8.0 months. Intraoperative stimulation at 0.5 mA was observed in 73% (33/45) of nerves, with 76% achieving full recovery, 18% partial recovery, and 6% no recovery. Two nerves stimulated at 2 mA and one at 20 mA, with both showing partial recovery. In contrast, 22% (10/45) of nerves showed no stimulation, leading to full recovery in 20%, partial recovery in 30%, and no recovery in 50% of cases. A significant (P < .001) association was found between stimulation thresholds and functional recovery. Conclusions: Intraoperative nerve stimulation is strongly linked to functional recovery postneurolysis, demonstrating its potential as a prognostic tool for guiding surgical decisions. Type of study/level of evidence: Prognostic, IV.